We appreciate power: A multimodal critical discourse analysis of Grimes' music video posted on youtube - Enguídanos Gómez, Adrià (Université autonome de Barcelone, 2019)
The aim of this dissertation is to produce a multimodal critical discourse analysis of Grimes' video We Appreciate Power. This will serve to explore issues of ideology, identity and multilingualism in both the music video and the YouTube polylogues generated in the same web page. In this work I suggest that Grimes adopts a poststructuralist view that inherits Haraway's cyborg concept (1991) in this piece of multimedia. I claim that Grimes wanted to show the conflictive moral boundaries that the idea of the cyborg and trans-humanism casts upon Western civilization, such as the loss of free will but also the transgression of problematic dichotomies. The fact that the comment section of the video is available to use might signal that Grimes wanted to raise awareness about trans-humanism. By doing virtual ethnography research, examples of discussion about the relationship between the video and the studied polylogues will be examined regarding the notions of the cyborg and multilingualism. Keywords: cyborg, multimodal critical discourse analysis, polylogue, virtual ethnography, YouTube.
Keywords: 2000 à aujourd'hui; 2010-2019; analyse de discours; arts; arts visuels et médiatiques; culture populaire; cyborg; discipline; ethnographie; femmes* artistes; médias sociaux; mémoires/thèses; périodes historiques; ressource en ligne; thématiques; écriture des femmes*

Surrounded: Skeena Reece - Reece, Skeena (Morris and Helen Belkin Art Gallery, 2019)
L'année dernière, la Belkin Art Gallery a eu le plaisir d'acquérir The Time It Takes (2017), l'œuvre d'art pour adultes de Skeena Reece, pour notre collection permanente. À cette époque, Reece a déclaré qu'elle avait toujours voulu travailler avec le berceau pour créer une série de photographies qui documenteraient son emballage de personnes spécifiques dans le sac de mousse. Comme le décrit Reece, "Le sac est un endroit pour se reposer un instant, évoquant un sentiment de nostalgie, pas un sentiment de perte. Être enveloppé donne un sentiment d'apaisement qui suscite de l'espoir pour l'avenir et est un moyen de tenir les gens debout. L'œuvre a commencé comme une performance pour The Fraud That Goes Under the Name of Love, une exposition de groupe à la SFU Audain Gallery de Vancouver en 2016. Elle a ensuite été présentée au Musée d'art contemporain de Montréal pour l'exposition de groupe Piriti: Scène contemporaine autochtone en 2017. La pièce a évolué en une installation pour Oboro, Montréal (2017) et Plug In ICA, Winnipeg (2018) respectivement.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; arts visuels et médiatiques; canada; cours; discipline; exposition; fem3100; performance; premier cycle; périodes historiques; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions